Sexual Offences in Genesis - Miller, James E. (Journal for the study of the Old Testament, 2000)
This paper studies the narrative patterns of sexual impropriety in Genesis, in particular incest, adultery and rape, noting the distinctive narrative patterns of each type of impropriety. Though Genesis recognizes incest between generations, it ignores incest within a generation, and adultery is characterized by avoidance. Also adultery seems to be exclusive of incest, occurring only outside the family boundaries. For the most part the cases studied are traditionally ascribed to J and provide a window into the mores of the narrator and audience.